Crucifix draped with purple cloth during Lent - Mumbai Archive Project Team (Jio Institute, 2024)
During Lent, the crucifix is draped with purple cloth, symbolizing mourning and sorrow for the suffering and death of Jesus. Purple, the liturgical colour for Lent, represents penance, humility, and sorrow for sin.